Quality of life in social housing in San Andres, Colombia, through bioclimatic air flow management (2015)
The article discusses the issue of social housing in the San Andrés and Providencia, Colombia. From multifamily housing model developed by the author for the National Pilot Program for Adaptation to Climate - INAP, Casaclima San Andrés Change, a series of simulations to evaluate the performance of the model in terms of flows of ventilation and temperature they are made relative humidity inside, under various conditions (open and closed windows, etc.). We conclude that the model, which incorporates technology wood construction, traditional in the archipelago, is a solution that provides thermal comfort to its inhabitants, and reduces environmental impact generated constructions in other materials, such as concrete.